The Rights of the Mortgagee Creditor and Their Effects Against Third Parties under the Saudi Registered Real Estate Mortgage Law (The International Journal for Scientific Research, 2026)
This study addresses the topic of "The Rights of the Mortgagee and Their Effects Against Third Parties According to the Saudi Registered Mortgage Law." This is a highly significant legal topic given the increasing expansion of real estate financing in the Kingdom of Saudi Arabia and the associated need for effective legal guarantees to protect creditors' rights and ensure stability in real estate and credit transactions.The study aims to clarify the nature and legal character of mortgages, analyze the rights granted to mortgagees, primarily the right of priority and the right of pursuit, and explain the impact of mortgage registration on its enforceability against third parties and the ranking of creditors. It also examines the rights of the possessor of the mortgaged property, the reasons for mortgage termination, and its legal consequences. The study employs a descriptive-analytical approach, reviewing and analyzing the regulatory texts governing mortgages in the Kingdom of Saudi Arabia and linking them to practical applications and relevant legal jurisprudence.The study reached several conclusions, most notably that mortgages are among the most prominent forms of real security that support real estate credit and achieve a balance between the interests of the mortgagee and the mortgagor. It also found that registering a mortgage is a fundamental requirement for its enforceability against third parties and for ensuring legal transparency. Furthermore, the study emphasized that the right of priority and the right of pursuit constitute the most important guarantees granted to the mortgagee, as they allow them priority in recovering their debt from the proceeds of the mortgaged property and in tracking the property regardless of who acquires it. The study also demonstrated that the Saudi legal system is committed to achieving a balance between protecting the rights of the mortgagee and protecting bona fide third parties by regulating registration and enforcement procedures and clarifying the rights of the holder of the mortgaged property.The study concluded that the Saudi legal system is careful to achieve a balance between protecting the rights of the mortgagee and protecting bona fide third parties by regulating registration and enforcement procedures and outlining the rights of the holder of the mortgaged property. The study recommended enhancing legal awareness of mortgage provisions, developing electronic registration and enforcement procedures, standardizing judicial principles related to mortgages, and supporting specialized legal studies in this field. This would contribute to strengthening real estate and credit stability and achieving the goals of Saudi Arabia's Vision 2030.
Keywords: Registered Mortgage; Mortgagee; Right of Priority; Right of Pursuit; Holder of Mortgaged Property; Real estate Registration; Real Estate Securities; Saudi Legal System